Happiness and Community-Specific Factors - Leerattanakorn, Nisachon; Wiboonpongse, Aree (Asian Journal of Applied Economics, 2017)
The majority of previous studies on happiness have mainly focused on individual factors, such as gender, age, income, educational level, and religion. Only a few studies have examined the role of community or society on individual happiness. This study analyzes the effects of community-specific factors on individual happiness using the survey data of 700 farmers in Thailand. The result of the ordered logit model reveals that community- (community economic strength and social capital) and individual-specific factors are significant determinants of individual happiness. Thus, previous studies that have ignored community environment have led to biased estimates of individual happiness. This study also proposes suggestions for policy makers.